2021
DOI: 10.1093/jpp/rgab057
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase and advanced glycation end products inhibition with Vernonia amygdalina root and leaf extracts: new data supporting the antidiabetic properties

Abstract: Objective This study aims to investigate antidiabetic activity of several Vernonia amygdalina extracts to study their potential use in medicine. Methods Aqueous and ethanol extracts were obtained by maceration and Soxhlet extraction from roots and leaves of V. amygdalina. The extracts were tested as inhibitors of α-glucosidase activity and of advanced glycation end products (AGEs) formation. Further, radical scavenging activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The oxygen radical absorbance capacity (ORAC) assay allows evaluating the ability of substances to interfere with oxidative reactions induced by peroxidic radicals. The assay was performed as previously reported [47,48]. Briefly, 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (trolox) was prepared in phosphate buffer in a concentration range of 6.25-50 µM.…”
Section: Measurement Of the Oxygen Radical Absorbance Capacitymentioning
confidence: 99%
“…The oxygen radical absorbance capacity (ORAC) assay allows evaluating the ability of substances to interfere with oxidative reactions induced by peroxidic radicals. The assay was performed as previously reported [47,48]. Briefly, 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (trolox) was prepared in phosphate buffer in a concentration range of 6.25-50 µM.…”
Section: Measurement Of the Oxygen Radical Absorbance Capacitymentioning
confidence: 99%
“…(Asteraceae), also known as ‘bitter leaf’ or ‘ndolé’ due to the bitter taste of the leaves, is an African and Asian medicinal plant well known for its use in traditional medicine in various diseases, including wound healing, malaria, hypertension, and DM [ 3 , 4 , 5 ]. Ethanol and aqueous Vernonia amygdalina (VA) extracts and their in vitro activity were studied as potential agents capable of counteracting hyperglycemia and the production of advanced glycation end products (AGEs), showing their activity against α-glucosidase activity and AGEs [ 6 ]. Furthermore, other authors have reported antidiabetic effects in diabetic rat models [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the presence in VA tissues of several phytochemicals, such as polyphenols, alkaloids, saponins, and steroid glycosides [ 6 , 15 , 16 ]. Although flavonoids are common compounds in many types of plants, which are also used for food, terpene-derived compounds are less documented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations